PRODUCTION OF "PODCAST KOMUNIKASI": AS AN ALTERNATIVE MEDIUM FOR LEARNING IN COMMUNICATION SCIENCE - Kutanto, Haronas; Jati, Rocky Prasetyo (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
This article is about the process and development of an audio podcast series titled "Podcast Komunikasi", driven by the recognition of communication science's pivotal role in contemporary society. Traditional educational media often struggle to effectively engage learners in this dynamic field, prompting the exploration of podcasting as an innovative learning medium. The primary objective is to bridge the gap between academic research and practical application, offering valuable insights into communication theory, practice, and trends for students and professionals. The "Podcast Komunikasi" aims to harness the popularity and accessibility of podcasts as a unique platform for communication science education. The content will be meticulously researched through a multidisciplinary approach that combines communication science expertise with podcast production skills to identify key topics and themes within the field. This ensures that the episodes are informative, relevant, and engaging. A collaborative team comprising communication experts, podcast producers, and audio engineers will work cohesively to script, record, and edit each episode, guaranteeing high-quality production and effective delivery of the subject matter. The podcast's accessibility will be enhanced by incorporating storytelling techniques and expert interviews, making it appealing to a diverse audience. The ultimate goal of this project is to publish the podcasts on platforms such as Anchor and Spotify. In conclusion, this initiative seeks to create an innovative and accessible medium for learning about communication science. The "Podcast Komunikasi" aspires to expand knowledge, encourage practical applications, and foster a thriving community of communication science enthusiasts by integrating research, expert collaboration, and compelling storytelling